Climate change and drought - Arnell N.W. (Drought management: scientific and technological innovations, 2008)
Climate change is likely to increase drought risk during the 21st century in many parts of the world. Climate model projections, under a range of emissions scenarios, consistently show that seasonal rainfall is likely to decrease across large parts of southern Europe, north Africa, central Asia and southern Africa, and reductions are also possible in other dry parts of the world. The effects of climate change, however, will be superimposed on the patterns of natural climatic variability - such as ENSO - and the effects of land cover change which also tends to lead to increased regional temperatures and lower regional rainfall. Quantitative estimates of change in drought risk are therefore very uncertain. Enhanced climate models, which can reproduce observed patterns of variability, will help reduce uncertainty in projected future changes, but drought management plans now need to begin to incorporate climate change. This can be done either through a scenario-based approach, where robustness of a plan is tested against different feasible stories, or through a risk-based approach using estimates of the likelihoods of defined drought outcomes. Both approaches have advantages and disadvantages.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)